Encapsulation of Temulawak Extract by Using Nanocrystalline Cassava and Sago Starches and Maltodextrin - Sunarti, Titi Candra; Pasaribu, Fatimah J; Winarti, Christina (UI Scholars Hub, 2020)
This study was conducted to evaluate the performance of Curcuma zanthorrhiza crude extract after encapsulated in nanocrystalline starch, and to investigate the effect of the ratio of nanocrystalline starches and maltodextrin; and the effect of concentration of temulawak extract on nanocapsule characteristics, as well as encapsulation effect on the stability of antioxidant activity. Preparation of nanocrystalline starch was conducted by using lintnerization and ethanol precipitation of cassava and sago starches. Nanocrystalline starch and maltodextrin were used as matrices with the ratio varied from 25:75, 50:50, and 75:25. The mixture of temulawak extract and matrices were homogenized and spray dried. Nanocapsules characteristics included the efficiency of encapsulation and drug loading, and antioxidant activity test were investigated. Nanocrystalline cassava and sago starches were potentially modified starch that can be used as the matrix for its low solubility and digestibility. It showed that the ratio of nanocrystalline starch, maltodextrin, and concentration of temulawak extract significantly influenced the nanocapsule characteristics. The best encapsulation condition obtained for nanocrystalline matrix from cassava starch with the ratio of nanocrystalline starch: maltodextrin 25:75 (%w/w) and 10% concentration of the temulawak extract, while for sago are 75:25 (%w/w) and 10% concentration of temulawak extract. Nanocrystalline matrix from cassava starch revealed higher encapsulation efficiency and antioxidant activity. The use of high temperatures during spray drying affected by the slight decline of antioxidant activity of encapsulated temulawak extract. Encapsulation of temulawak extract by using nanocrystalline starch and maltodextrin could retain and protect its antioxidant activity.